Damage assessment using modeling of large-scale confined masonry building - Escudero Torres, Cuauhtemoc (2018)
The seismic behavior of a representative medium-rise building of Mexico City is evaluated using the capacity spectrum method. This method is widely used in the seismic assessment of buildings because it allows obtaining fragility curves which permit evaluating the ability of a building to resist earthquakes. A real full-height multistory model is proposed to test the capabilities of the algorithm exhibited. The model is outlined through structural drawings sized and structured in accordance with building code regulations for masonry structures in Mexico City. Computational requirements for the analysis of large structures are indicated in addition to improvements to a nonlinear computing code for better performance in terms of memory management and execution times. Finally, a comparison of obtained results and building code regulations is carried out, highlighting differences in the obtained results. The need to handle meshes with a high number of finite elements (FEs) led to development of a new layered finite element that can reproduce the nonlinear behavior of its constituent materials when there are out-of-plane stresses without having to introduce additional degrees of freedom. The proposed FE is compared with the standard FE, presenting different kinematics, and excellent results are obtained. This work emerges from the need to combine and improve existing technologies in the field of finite-element analysis. One such technology is the numerical simulation of the behavior of composite materials. Therefore, it was also necessary to develop a computing program capable of reading both finite-element meshes and patterns of fibers to calculate the information of the composite materials, such as volumetric participation and fiber’s orientation.